PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN FRAUD DANA DESA: STUDI KASUS DESA DI KECAMATAN JATEN - Nafisah Emir; Rispantyo Rispantyo (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This research aims to analyze the influence of accountability, transparency, and whistleblowing system on the prevention of Village Fund Fraud in Jaten Subdistrict, Karanganyar Regency. A quantitative approach was employed, untilizing primary data from 40 village officials selected throught purposive sampling. Data analysis was conducted using multiple linier regression with SPSS assistance, following validity, reliability, and classical assumption tests. The findings reveal that accountability, transparency, and whistleblowing system have a positive and significant effect on fraud prevention. The results indicate that enhancing accountability, information openness, and effective violation reporting mechanisms can strengthen efforts to prevent fraud in village Fund management.